Slum Health: Arresting COVID-19 and Improving Well-Being in Urban Informal Settlements - Corburn, Jason; Vlahov, David; Mberu, Blessing; Riley, Lee; Caiaffa, Waleska Teixeira; Rashid, Sabina Faiz; Ko, Albert; Patel, Sheela; Jukur, Smurti; Martínez-Herrera, Eliana; Jayasinghe, Saroj; Agarwal, Siddharth; et al. (Springer Link, 2022)
This article was published in Springer Link [ Copyright © 2020, The New York Academy of Medicine] and the definite version is available at: https://doi.org/10.1007/s11524-020-00438-6 The Journal's website is at: https://link.springer.com/article/10.1007/s11524-020-00438-6#rightslink